Coastal and Marine Environments Physical Processes and Numerical Modelling - Simão Antunes Do Carmo, José (IntechOpen, 2020)
This book systematizes the concepts of contemporary coastal zone management and suggests possible structural and non-structural management tools for decision-making processes. Some successful adaptation measures and case studies on oceanic processes and coastal protection are discussed. High-frequency communications in coastal and marine environments are also addressed.All chapters contribute relevant information and useful content to scientists and other readers interested or concerned about the lack of adequate management actions and the installation of appropriate protections or their ineffectiveness in containing coastal vulnerabilities and risks.